2017
DOI: 10.1093/humrep/dex284
|View full text |Cite
|
Sign up to set email alerts
|

Differing molecular response of young and advanced maternal age human oocytes to IVM

Abstract: J.M.R. was supported by an Austin Eugene Lyons Fellowship awarded by the University of California, Davis. The Eunice Kennedy Shriver National Institute of Child Health and Human Development of the National Institutes of Health (awarded to P.J.R.; R01HD070044) and the Fertility Laboratories of Colorado partly supported the research presented in this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 43 publications
3
57
1
Order By: Relevance
“…High throughput techniques are widely applied to understand time-dependent global changes in gene expression during oocyte maturation, oocyte-to-embryo transition and early embryogenic development, often with special attention to human infertility [42]. Even though, methodical improvements of NGS methods have led to the establishment of suitable protocols for transcriptomic studies of mammalian oocytes, no such approach is available for deep-sequencing of polysome-bound mRNAs [55,56]. High quality polysome profiling has conventionally required large number of cells to obtain well-defined and interpretable peaks (e.g., for HeLa cells approximately 2-4 × 10 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…High throughput techniques are widely applied to understand time-dependent global changes in gene expression during oocyte maturation, oocyte-to-embryo transition and early embryogenic development, often with special attention to human infertility [42]. Even though, methodical improvements of NGS methods have led to the establishment of suitable protocols for transcriptomic studies of mammalian oocytes, no such approach is available for deep-sequencing of polysome-bound mRNAs [55,56]. High quality polysome profiling has conventionally required large number of cells to obtain well-defined and interpretable peaks (e.g., for HeLa cells approximately 2-4 × 10 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the current studies were performed in the mouse, TRPM7, CACNA1H, and TRPV3 are all expressed in human oocytes and TRPM7 and TRPV3 are expressed in macaque oocytes as indicated by RNA sequencing (45)(46)(47)(48). Furthermore, there are numerous missense or loss of function (LoF) mutations identified in human TRPM7 (480 missense, 27 LoF), CACNA1H (1,045 missense, 10 LoF), and TRPV3 (312 missense, 23 LoF) (see Exome Aggregation Consortium browser at exac.broadinstitute.org; ref.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the oocyte MPF complex is not well characterized [309]. CDK1 [25,79,80], CDC25 [25,84], and WEE2 are expressed in human oocytes [80]. Sang et al found WEE2 mutations in four women with fertilization failure [83].…”
Section: Oocyte Maturation Promoting Factor: Cyclin-dependent Kinase mentioning
confidence: 99%
“…Reyes et al studied molecular responses in 10 oocytes (5 GV, 5 MII) from young women and 10 oocytes (5 GV, 5 MII) from older women using RNA-Seq sequencing (HiSeq 2500; Illumina) [79]. Patients were stimulated with FSH and triggered with HCG.…”
Section: Oocyte Quality and Ivmmentioning
confidence: 99%